Acute Striato-Cortical Synchronization Induces Focal Motor Seizures in Primates. (8th August 2020) - Aupy, Jerome; Ribot, Bastien; Dovero, Sandra; Biendon, Nathalie; Nguyen, Tho-Hai; Porras, Gregory; Deffains, Marc; Guehl, Dominique; Burbaud, Pierre
Abstract: Objective: Whether the basal ganglia are involved in the cortical synchronization during focal seizures is still an open question. In the present study, we proposed to synchronize cortico-striatal activities acutely inducing striatal disinhibition, performing GABA-antagonist injections within the putamen in primates. Method: Experiments were performed on three fascicularis monkeys. During each experimental session, low volumes of bicuculline (0.5–4 μL) were injected at a slow rate of 1 μL/min. Spontaneous behavioral changes were classified according to Racine's scale modified for primates. These induced motor behaviors were correlated with electromyographic, electroencephalographic, and putaminal and pallidal local field potentials changes in activity. Results: acute striatal desinhibition induced focal motor seizures. Seizures were closely linked to cortical epileptic activity synchronized with a striatal paroxysmal activity. These changes in striatal activity preceded the cortical epileptic activity and the induced myoclonia, and both cortical and subcortical activities were coherently synchronized during generalized seizures. Interpretation: Our results strongly suggest the role of the sensorimotor striatum in the regulation and synchronization of cortical excitability. These dramatic changes in the activity of this "gating" pathway might influence seizure susceptibility by modulating the threshold for the initiation of focal motor seizures.